Assessment of Drug-Food Interactions Knowledge among Pharmacy Students at AL-Muthanna University in Iraq - Razzaq, Safa Azhar (American Journal of Biomedicine and Pharmacy, 2025)
Drug-food interactions (DFIs) are a critical yet often underrecognized factor in medication safety and therapeutic efficacy. Despite their significance, pharmacy students’ knowledge regarding DFIs remains insufficiently explored, particularly in Iraq. This study aimed to assess the awareness and understanding of DFIs among undergraduate pharmacy students at Al-Muthanna University through a descriptive cross-sectional online survey conducted in August 2024. The questionnaire covered demographic data and evaluated knowledge across multiple DFI scenarios. Results from 94 participants revealed that while the majority demonstrated good awareness of common interactions—such as those involving tetracycline and dairy, or grapefruit and CYP3A4 substrates—knowledge gaps were evident in areas like warfarin and dietary vitamin K, or digoxin and fiber. These findings emphasize the necessity of integrating structured DFI education into the pharmacy curriculum to enhance future pharmacists’ competency in reducing food-related medication errors and improving patient counseling.